ChemInform Abstract: A Highly Efficient Catalyst of a Nitrogen‐Based Ligand for the Suzuki Coupling Reaction at Room Temperature under Air in Neat Water. Issue 47 (6th November 2014) - Liu, Shiwen; Lv, Meiyun; Xiao, Daoan; Li, Xiaogang; Zhou, Xiuling; Guo, Mengping
Abstract An air‐stable and water‐soluble PdCl2—glycine complex exhibits excellent catalytic activity in the reaction of aryl halides (I) containing a carboxyl group with various boronic acids (II) (24 examples).